Children’s perspectives on child well-being : a pathway to sustainable futures. A case study in the Brits and Rustenburg areas in North West Province - Le Roux, Magdalena Petronella (University of Pretoria, 2025)
Mini Dissertation (MSW (Play-based Intervention))--University of Pretoria, 2024.